Environmental software systems : data science in action : 13th IFIP WG 5.11 International Symposium, ISESS 2020, Wageningen, The Netherlands, February 5-7, 2020, Proceedings /: data science in action : 13th IFIP WG 5.11 International Symposium, ISESS 2020, Wageningen, The Netherlands, February 5-7, 2020, Proceedings. (2020) - Unknown
No abstract available